Heterologous expression of the insect SVWC peptide WHIS1 inhibits Candida albicans invasion into A549 and HeLa epithelial cells - Chen, Ming; Huang, Wei-Kang; Yao, Yang; Wu, Shi-Mei; Yang, Yong-Xin; Liu, Wen-Xia; Luo, Gang; Wei, Shao-Feng; Zhang, Hua; Liu, Hong-Mei; Wang, Bing (Frontiers in Microbiology, 2024)
C. albicans, a microbe commonly isolated from Candida vaginitis patients with vaginal tract infections, transforms from yeast to hyphae and produces many toxins, adhesins and invasins, as well as C. albicans biofilms resistant to antifungal antibiotic treatment. Effective agents against this pathogen are urgently needed. Antimicrobial peptides (AMPs) have been utilized to cure inflammation and infectious diseases. Here, we isolated WHIS1, a novel insect SVWC peptide from whole housefly larvae. The expression pattern of WHIS1 showed a response to C. albicans stimulation. In contrast to other SVWC members, which function as antiviral peptides, IFN analogues or PRRs, the prokaryotically expressed MdWHIS1 protein inhibits C. albicans growth. Eukaryotic heterologous expression of WHIS1 inhibited C. albicans invasion into A549 and HeLa cells. The heterologous expression of WHIS1 clearly inhibited hyphal formation both extracellularly and intracellularly. Furthermore, mechanistic research has demonstrated that WHIS1 downregulates all key hyphal formation factors (ALS1, ALS3, ALS5, ECE1, HWP1, HGC1, EFG1, and ZAP1) both extracellularly and intracellularly. These data showed that heterologously expressed WHIS1 inhibits C. albicans invasion into epithelial cells by affecting hyphal formation and adhesion factor-related gene expression. These findings provide new potential drug candidates for treating C. albicans infection.